Analysis of Factors Influencing Students' Learning Difficulties in Economics at SMAN 3 Langgam - Nina Anjayani Rambe; Suarman Suarman; Hendripides Hendripides (Journal of Education Technology Information Social Sciences and Health, 2024)
This study aims to determine the factors that influence students' learning difficulties in economics subjects. This research is included in survey research with 72 students as respondents using a quantitative descriptive method. Source of data obtained by means of a questionnaire, then analyzed using descriptive analysis. The results showed that the factors that influence student learning difficulties are internal factors and external factors. Thus the factors that influence student learning difficulties are not only determined by internal factors from the motivation sub-indicator which are in the high category, but are also influenced by external factors from the teacher sub-indicator which are in the very high category.